Effect of Sexual Function Improvement Program for Breast Cancer Survivors on Sexual Distress, Sexual Satisfaction and Marital Intimacy - Duck Hee Moon (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study was conducted to examine effects of a sexual function improvement program on sexual distress, sexual satisfaction and marital intimacy among breast cancer survivors. METHODS: With quasi-experimental design, a total of 54 women after breast surgery were assigned into experimental group (n=28) and control group (n=26) after recruited via convenience sampling. They were endocrine surgery outpatients in university hospital at Chonnam province. Experimental group received a sexual function improvement program 5 sessions over 5 weeks. Sexual distress, sexual satisfaction, and marital intimacy were examined with self-report structured questionaries. Data were analyzed using ?2 test, Fisher's exact, independent t-test, and analysis of covariance with SPSS 17.0/window program. RESULTS: Women who participated in the sexual function improvement program had lower sexual distress (F=27.29, p<.001), higher sexual satisfaction (t=3.09, p=.003) higher marital intimacy (F=17.51, p<.001) than the women who did not participate. CONCLUSION: Results suggest that a sexual function improvement program can be effective strategy to improve sexual distress, sexual satisfaction and marital intimacy. Therefore, this program can be regarded as useful nursing intervention program for breast cancer survivors.